Mechanisms underlying the cytotoxic effect of propolis on human laryngeal epidermoid carcinoma cells - Frión-Herrera, Yahima [UNESP]; Díaz-García, Alexis; Ruiz-Fuentes, Jenny; Rodríguez-Sánchez, Hermis; Maurício Sforcin, José [UNESP] (Taylor & Francis, 2018)
Propolis has been used as a traditional remedy for centuries because of its beneficial effects, including anticancer properties. The aim of this study was to compare the cytotoxic mechanism of Cuban red propolis (CP) and Brazilian green propolis (BP) on human laryngeal carcinoma (HEp-2) cells. Cell viability, leakage of lactate dehydrogenase, fluorescence staining, mitochondrial membrane potential (ΔΨm) and the expression of pro/anti-apoptotic genes were assessed. Cell viability and cytotoxic assays suggested a dose-dependent effect of CP and BP extracts with a possible association of intracellular reactive oxygen species production and decreased ΔΨm. Both samples induced apoptosis via activation of TP53, CASP3, BAX, P21 signalling, and downregulation of BCL2 and BCL-XL. CP exerted a higher cytotoxic effect than BP extract. Our findings suggest further investigation of the main components of each propolis sample, what may lead to the development of strategies for the treatment of laryngeal cancer.
Keywords: apoptosis; cytotoxicity; HEp-2 cells; Propolis